2005
DOI: 10.1093/annonc/mdi221
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor activating mutations in Spanish gefitinib-treated non-small-cell lung cancer patients

Abstract: EGFR TK mutational analysis is a novel predictive test for selecting lung adenocarcinoma patients for targeted therapy with EGFR TK inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
108
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(126 citation statements)
references
References 20 publications
15
108
1
1
Order By: Relevance
“…The PCR and sequencing protocol was performed to amplify and sequence exons 19 and 21 of EGFR,exons 1 and 2 of KRAS, and exons 15 of BRAF in order to detect EGFR, KRAS and BRAF mutations using the primers described previously (10)(11)(12). Purified PCR products were sequenced on an automatic DNA sequencer (ABI 3130 Genetic Analyzer, Applied Biosystems).…”
Section: Mutation Analysismentioning
confidence: 99%
“…The PCR and sequencing protocol was performed to amplify and sequence exons 19 and 21 of EGFR,exons 1 and 2 of KRAS, and exons 15 of BRAF in order to detect EGFR, KRAS and BRAF mutations using the primers described previously (10)(11)(12). Purified PCR products were sequenced on an automatic DNA sequencer (ABI 3130 Genetic Analyzer, Applied Biosystems).…”
Section: Mutation Analysismentioning
confidence: 99%
“…Approximately 10% of NSCLCs from the United States and Europe harbor EGFR somatic mutations, as do approximately 30-50% of tumors from patients from East Asia. [7][8][9][10][11][12][13][14][15][16][17][18] The clinical responses in patients with NSCLC treated with gefitinib and erlotinib are highly correlated with the presence of EGFR somatic mutations 6,7,[12][13][14][15][16]19,20 and/or increased copy number of EGFR. 19,21,22 While therapies directed against a target activated by somatic mutations often yield dramatic clinical responses, many patients eventually become resistant to these therapies upon the acquisition of secondary mutations in the original target gene.…”
Section: Introductionmentioning
confidence: 99%
“…These studies also showed signifi cantly higher overall survival rate in EGFR-mutant patients compared to wild type patients (>2 years vs. 8 months) (Uramoto and Mitsudomi, 2007). And among the lung carcinoma patients, Asian ethnic group showed EGFR mutation frequencies of 22-67% followed by patients in South Europe (10-24%), and patients in North America (3-25%) (Marchetti et al, 2005;Lynch, et al, 2004;Paez et al, 2004;Pao et al, 2004;Uramoto and Mitsudomi, 2007;Cortes-Funes et al, 2005;Eberhard et al, 2005;Sequist et al, 2006). These results provided valuable insights how to screen patients who would respond well to the treatment and paved the way to the future strategies of cancer treatment based on the predictive biomarkers of patients and not simply based on the tumor types.…”
Section: Future Cancer Therapy: Personalized Medicinementioning
confidence: 89%